2013
DOI: 10.1001/jamadermatol.2013.2440
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation Between Balanitis and Carcinoma In Situ Using Reflectance Confocal Microscopy

Abstract: We were able to differentiate between balanitis and CIS. Reflectance confocal microscopy may help to avoid biopsies at this sensitive site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Similar lesions in other mucosal sites, such as the vaginal, perianal, and oral regions, have been reported [7, 12, 13]. Reflectance confocal microscopy may help avoid penile biopsy by differentiating between balanitis and carcinoma in situ [14]. …”
Section: Discussionmentioning
confidence: 68%
“…Similar lesions in other mucosal sites, such as the vaginal, perianal, and oral regions, have been reported [7, 12, 13]. Reflectance confocal microscopy may help avoid penile biopsy by differentiating between balanitis and carcinoma in situ [14]. …”
Section: Discussionmentioning
confidence: 68%
“…However, it has been suggested that the presence of plasma cell infiltrate is relatively not specific for the diagnosis of PCVZ [22,24]. Recently, reflectance confocal microscopy, an in vivo imaging method to get morphological information about architecture and single cells in the skin, was shown to be helpful in differentiating between balanitis and carcinoma in situ and avoiding biopsies at this sensitive site [25]. …”
Section: Discussionmentioning
confidence: 99%
“…[25] Generally, genital skin is suitable for confocal microscopy because of its thin or absent cornified layer. It is very useful tool to differentiate ZB from CIS.…”
Section: Diagnosismentioning
confidence: 99%
“…The most relevant features for CIS on RCM are atypical honeycomb pattern, disarranged epidermal pattern/focal loss, and round nucleated cells. [25] A nucleated honeycomb pattern and vermicular vessels is a clue for benign inflammatory genital skin disease. In contrast to this, the adjacent normal skin shows a typical honeycomb pattern and round papillary vessels.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation